CLIMATE SMART VARIETIES OF GROUNDNUT SUITABLE FOR SCARCE RAINFALL AGRO CLIMATIC ZONE OF ANDHRA PRADESH - B , SAHADEVA REDDY (The Journal of Research ANGRAU, 2026)
A field experiment was carried out to evaluate the influence of wet and dry spells on groundnut varieties in scarce rainfall agro climatic zone under rainfed conditions for two consecutive years during kharif 2022 and 2023 at AICRPDA, Agricultural Research Station, Ananthapur of Andhra Pradesh. Among groundnut varieties tested during wet spell of 2022, Kadiri Lepakshi (2635 kg/ha) followed by TCGS 1694 (1900 kg/ha) recorded higher pod yield when compared to other varieties tested. During drought year of 2023, TCGS-1694 recorded significantly higher pod yield when compared to other tested varieties with rain water use efficiency of 4.42 kg/ha mm. TCGS-1694 proved as the top climate resilient groundnut variety for scarce rainfall agro climatic zone of Andhra Pradesh, maintaining high pod yields (1556 -1900kg ha-1), haulm yields (2,834-3,289 kg ha-1), and superior rain water use efficiency (3.80-4.42 kg ha-1mm) across wet and dry extremes. Kadiri Lepakshi proved ideal for high rainfall events (2,635 kg ha 1 pod yield), extreme while Nithya Haritha and K-9 showed consistent intermediate performance.